Adult development and aging : biopsychosocial perspectives - Whitbourne, Susan Krauss. (John Wiley and Sons, 2001)
Themes and issues in adult development and aging. Models of development. The study of adult development and aging. Physical and sensory changes in adulthood and old age. Chronic disease and health. Information processing, attention, and memory...